Liraglutide as an innovative and multifunctional drug for patients with obesity – the current state of knowledge and future prospects - Grodkiewicz, Maria; Kozieł, Paweł; Artykiewicz, Klaudia; Gorczyca, Kamila; Czarkowski, Marcin; Słupczyńska, Aleksandra; Urbaś, Weronika; Podgórska, Klaudia; Puła, Aleksandra; Krzysiek, Urszula (Journal of Education, Health and Sport, 2022)
Obesity is considered a disease of civilization representing a global health and social problem. Currently, 21% of adult Poles suffer from obesity, so every fifth patient contacted by a doctor is obese. Obesity is a chronic disease, associated with excessive accumulation of adipose tissue, which causes a deterioration in the health and quality of life of an obese patient. It also consequently leads to an increased risk of developing many diseases - including cardiovascular, metabolic and neoplastic diseases. Excessive body weight ranks sixth in importance as a risk factor responsible for the number of deaths worldwide. The mainstay of obesity treatment is lifestyle modification. It includes changing eating habits and increasing physical activity. However, due to the high prevalence of obesity in developed countries, its serious consequences and the unsatisfactory effect of weight loss in some patients with an appropriate diet, pharmacological methods of obesity treatment were searched for. Currently, there are three drugs approved for the treatment of obesity in Poland: orlistat, a combined preparation of naltrexone + bupropion and liraglutide – agonist of a glucagon-like peptide-1 receptor. The effectiveness of one of them - liraglutide - is particularly significant, and the effect of this drug in reducing cardiovascular risk is also promising, which is extremely important in obese patients. For this reason, in the latest recommendations of the Polish Obesity Treatment Association, liraglutide is indicated as the drug of first choice for obese or overweight patients with a BMI ≥27 kg / m2, in whom coexisting: pre-diabetes, type 2 diabetes, arterial hypertension, polycystic ovary syndrome, nonalcoholic fatty liver disease, metabolic syndrome, atherosclerosis or sleep apnea syndrome. Due to the presence of GLP-1 receptors in many organs, the use of liraglutide in the future would probably extend to more diseases than obesity and type 2 diabetes.